MADRASAH PROBLEM DAN SOLUSI PENGEMBANGANNYA - Efendi, Dedi; Aprison, Wedra (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
The main problems in this writing are Madrasah Problems and Development Solutions, in this journal the problems found are the condition of teachers who are not sufficient, the lack of educational facilities and infrastructure, curriculum, too many fields of study taught, little assistance from the government, causing schools to become operational. slow.The purpose of this discussion is to explain this writing is Madrasah Problems and Development Solutions. The type of research that the writer did was field research which is a qualitative description. Data collection techniques that the authors use are through observation, interviews, and documentation. The validity of the data used is triangulation. The analysis technique that the writer uses according to Miles and Huberman. From the results of the research on Madrasah Problems and Development Solutions, the problems faced by madrasas are: Inadequate teacher conditions, lack of educational facilities and infrastructure, curriculum, low school student performance, too many fields of study being taught, the curriculum does not refer to the interests of students, there are changes or improvements to the 2013 curriculum, lack of teaching aids and laboratories, the economic level of students' parents are mostly middle to lower, the small contribution from the government.